Effect of wheat seed priming on the resistance against allelopathic stress of extract resulted from differentparts of Field bind weed ( Convulvulus Arvensis L.) in germination stage - مریم ادیبی; سعید وزان; قاسم توحید لو (علوم و فناوری بذر ایران)
In order to evaluate seed priming effects on resistance of wheat germination against allelopathic stress caused by various bindweed (Convulvulus arvensis L.) organs, a study was carried out as factorial experiment in completely randomized design with four replications in research laboratory of Karaj agriculture faculty (2012).  Treatments were seed priming (distilled water, hydropriming and osmopriming with 15 and 45 ds/m of urea for eight hours), wheat cultivars (Niknezhad and Pishtaz), extracts of various bindweed organs (leaves, stem, root and total plant) and various extract concentrations (25, 50 and 100%). Results showed that extract didn’t affect germination percentage and plumule length but radicle length was increased by various concentrations of extract in hydroprimed seeds. The highest reduction in plumule length was observed in total plant extract whereas stem extract caused the highest radicle reduction. According to the results, Niknezhad cultivar showed superiority in all treatments because of better plumule and radicle length.Root lengthin seedprimingwithwater under Extractconcentration in Niknezhad 27/54per cent and thecultivar Pishtaz14/45percentlower than the control was reducedAlso water hydropriming could reduce the negative effects of bindweed extract on radicle length.